Evaluation of Pain Perception During Local Anaesthetic Administration with Conventional vs Insulin Syringe: An In-Vivo Study (Academia Journal of Medicine, 2025)
Aim: This study aimed to evaluate and compare pain perception during the administration  of local anesthetic solution using conventional syringes versus insulin syringes in pediatric  patients aged 6-8 years. Materials and Methods: A total of 40 patients requiring maxillary local infiltration were  recruited. Participants were randomly assigned to receive local anesthetic via either a  conventional syringe or an insulin syringe. Pain perception was assessed using a Visual  Analogue Scale (VAS), where 0 represented no pain and 10 represented the worst pain  imaginable. Measurements were taken immediately following the administration of the  anesthetic. Results: The analysis of the VAS scores demonstrated that patients who received the  anesthetic via insulin syringes reported significantly lower pain levels compared to those  who received it via conventional syringes (p < 0.05). The results indicate a clear preference  for the insulin syringe method, suggesting reduced pain perception. Conclusion: The study concluded that the use of insulin syringes for local anesthetic  administration in pediatric dental procedures may lead to a significantly lower pain  experience compared to conventional syringes.
Keywords: Local Anesthesia; Pain; Pediatric Patient; Insulin Syringe